Tele-Konsultasi Kebidanan di Era Pandemi Covid-19, “Gratis: Mari Bertanya: Konsultasi Kesehatan Ibu, Bayi dan Kesehatan Reproduksi Wanita Bersama Bidan Profesional” - Indria Astuti; Syara Al-Fajar Shitah; Rani Sumarni (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The Covid-19 pandemic forces us to do everything from home; this impacts access to maternal, child, and reproductive health services. Recent research has shown that coronavirus infection is similar to HIV, which has a similar gene mutation, which means it can attack human cells 1,000 times stronger than the SARS virus. Therefore, President Jokowi has instructed to carry out activities at home, in which health services are also limited. Many concerns occur in the community, especially among pregnant women, so that even pregnant women cannot access health services and postpartum mothers, infants, and mothers who are family planning acceptors. The latest data from the BKKBN shows a national decline in family planning services from February to March; almost 50% of family planning services in each type of family planning have decreased; one of the factors is the lack of information and education to the public, how to use safe contraception during pregnancy this pandemic. This community service aims to help with problems regarding the difficulty of accessing health services due to the pandemic, and this activity is a form of devotion to the midwifery study program and the profession in the country. Implementing this community service uses internet access and communication tools, both laptops and the internet. The main activity of this community service is to provide online midwifery consultation via text, voice, and video. 100% stated that they were satisfied with the counselor's services provided 90% of clients noted that this online consultation helped solve their problems experienced clients.